Peculiarities of histological structure of some organs of serotine bat (Eptesicus serotinus) - Serdioucov, J.; Filipets, Y.; Shkundia, D.; Kruchynenko, O. (Regulatory Mechanisms in Biosystems, 2023)
Chiroptera is the only group of mammals that is able to fly. They are beneficial for people and ecosystem they live in. In Ukraine, all species of bats are rare or endangered, in particular serotine bat (Eptesicus serotinus Schreber, 1774). So as to prevent the extinction of currently existing species of bats, it is crucial to combat their diseases, in particular improve diagnostics, including postmortem diagnostics. At the macroscopic and microscopic levels, morphology of bats has still been studied poorly, especially such of bats that live in Ukraine. Besides, knowledge of the structure of various organs of bats at macroscopic and microscopic levels is necessary for effective pathoanatomic diagnostics of their diseases. We researched the normal histological structure of some organs of E. serotinus. For this purpose, we used four corpses of this animal, which had previously died as a result of their disturbance during winter hibernation. We carried out a histological study, for which we sampled organs such as the liver, kidneys, lungs, heart, subcutaneous gland, and spleen. From the samples, we prepared histological sections and stained them with hematoxylin eosin. We described the general patterns of microscopic structure of the said organs of serotine bat. We found that microscopic structure of all the examined organs was similar to that of mammals in general. At the same time, we did observe some peculiarities of the histological structure of the studied organs, especially lungs, compared with such of other mammals, particularly: poor degree of development of the stroma, compact arrangement of parenchyma elements in the parenchyma-structure organs, large variability of sizes of alveolar lumens in the lungs. We assume that those peculiarities had emerged because of bats’ adaptation for flight. We believe that it is promising to continue research of microscopic structure of various organs of E. serotinus, as well as other bats living in Ukraine and around the globe.